Lexical Cohesion Analysis of Will Smith’s Full Interview with Ellen - Sagala, Juni Arta; Mubarak, Zia Hisni (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study's objective is to determine the types of lexical cohesion employed in